2000W Blue laser directed energy deposition of AlSi7Mg: process parameters, molten pool characteristics, and appearance defects. Issue 1 (1st January 2023) - Tang, Zijue; Wei, Qianglong; Gao, Zhenyang; Yang, Huihui; Wang, An; Wana, Le; Luo, Cheng; Wu, Yi; Wang, Haowei; Wang, Hongze
ABSTRACT: Aluminium alloys are difficult to be manufactured by directed energy deposition (DED) with the widely used infrared laser because of the low absorptivity. A blue laser with a 450 nm wavelength has a significantly higher laser absorptivity in processing aluminium. Here, we developed a 2000 W blue laser directed energy deposition (BL-DED) system for additive manufacturing. In this system, a coaxial camera, a paraxial high-speed camera, and a paraxial infrared camera were simultaneously adopted to analyze the formation and evolution of molten pool characteristics. The relationships among the molten pool characteristics, depositing states, and appearance defects were built. We successfully printed the curved thin wall with good appearance quality by the manual in-situ control of appearance defects. This work demonstrated the advantages of the blue laser in DED of aluminium alloy, which could melt the powders under lower energy input conditions and result in a more stable deposition process.